Treatment of Familial Hypercholesterolemia with Intracranial Xanthoma: Case Report - Kou, XiaoBo; Liu, LunXin; Zhou, LiangXue (Frontiers in Surgery, 2022)
Intracranial xanthoma is a rare benign intracranial tumor. It often occurs in patients with hyperlipidemia. Intracranial xanthomas grow slowly, and clinical symptoms only appear when the mass compresses the surrounding tissues, so early diagnosis of the disease is difficult.